Design of a Symmetric Hybrid Graphene Plasmonic Waveguide with High Confinement and Efficiency - Mohammad Reza Jafari; Akbar Asadi; Somaye Karimi (فیزیک کاربردی ایران)
Plasmons in graphene have unusual properties and offer promising prospects for plasmonic applications covering a wide frequency range from terahertz to the visible spectrum, and many studies have been conducted on plasmon modes in graphene. In this research, a symmetric graphene plasmonic waveguide has been proposed to improve the waveguide performance in the mid-infrared range, and the plasmonic properties of graphene have been investigated by the finite element method and using COMSOL software. The structure of this waveguide is in the form of two elliptical nano-cylinders coated with graphene, which are placed symmetrically on each side of a thin sheet of Al2O3. The results obtained from the simulation show that by changing the geometric parameters of the proposed structure and changing the type of materials, the propagation length of the modes is more than 8 micrometers, and the normalized mode area is obtained in the order of 10-6. For this reason, the proposed waveguide has promising applications in photonic integrated circuit components and other nanoscale devices.